Pawn (RAHN) In The Perspective Of The Hadith Of The Prophet Muhammad SAW - Muhammad Satar; La Ode Ismail Ahmad (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The life advocated and described in Islamic Law is to live by helping each other in various ways. In this regard, loans based on Islamic law provide certainty of benefits for its creditors. The term pawn transaction where in Islam is Rahn. A lien or Ar-Rahn is an agreement for the granting of property as collateral for what will be borrowed or in this case a debt that will be carried out as a guarantor when the creditor is unable to pay off the debt. Islam basically allows a lien transaction where a person obtains goods by paying them first and then agrees between the debtor and the creditor provided that the creditor or borrower must provide guarantees to the debtor. The guarantee or marhun and the value of its use used as a guarantor is a right for the borrower which is not allowed to be used by the guarantor. Instead, there must be permission from the debtor or borrower.